Correcting promoter and beta-lactamase ORF orientation in a widely-used retroviral plasmid to restore bacterial growth - Jürgen Wittmann (Scientific Reports)
Abstract The pBMN-I-GFP plasmid is a widely used retroviral vector for producing retroviral particles, utilized by thousands of laboratories worldwide. However, we observed that E. coli transformed with pBMN-I-GFP failed to grow on selective LB agar plates containing ampicillin or carbenicillin, in contrast to similar retroviral vectors. Multiple attempts to optimize growth conditions were unsuccessful. Sequencing, contrary to the available reference sequence, revealed an inversion of the beta-lactamase (bla) gene and part of its promoter, likely disrupting bla expression and, consequently, antibiotic resistance. To address this, we corrected the orientation of the ampicillin resistance gene and its promoter in a new plasmid, prBMN-I-EGFP. This modification restored robust growth of E. coli transformed with this plasmid on selective plates, confirming the essential role of an intact bla promoter for antibiotic resistance. Additionally, retroviral functionality tests in murine cell lines showed that prBMN-I-EGFP exhibited transfection and infection efficiencies comparable to the original pBMN-I-GFP. These findings underscore the importance of thorough sequence verification for commonly used plasmids and present an improved version of pBMN-I-GFP.